2009
DOI: 10.1590/s0100-204x2009000800004
|View full text |Cite
|
Sign up to set email alerts
|

State of the science and the way forward for the ecotoxicological assessment of contaminated land

Abstract: -Over the past two decades, soil ecotoxicologists have made strides in utilizing the basic concepts and advancements in soil zoology and ecology. They have applied the existing tools, and developed new ones to investigate how chemical contamination can affect soil ecosystems, including the degradation or destruction of soil quality and habitats or the diminishment of belowground biodiversity. Soil ecotoxicologists are applying a suite of standard protocols, originally developed as laboratory tests with single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 29 publications
0
17
0
5
Order By: Relevance
“…The latter were then separated into two groups based mainly on their OM content, with group 1 generally presenting lower values than group 3. The reference soil allocated to each of the three soil groups was selected so that its characteristics matched, to the extent possible, these three soil properties, which are known to influence not only the bioavailability of contaminants (Kuperman et al 2009), but also the avoidance response of the two tested soil-dwelling species (Natal-daLuz et al 2008). The heterogeneity of the soil inside the smelter area can be related to the failed attempt to encapsulate the tailings by depositing thousands of cubic meters of soil from regions around (Anjos 2003).…”
Section: Soil Properties and Selection Of Reference Soilsmentioning
confidence: 99%
“…The latter were then separated into two groups based mainly on their OM content, with group 1 generally presenting lower values than group 3. The reference soil allocated to each of the three soil groups was selected so that its characteristics matched, to the extent possible, these three soil properties, which are known to influence not only the bioavailability of contaminants (Kuperman et al 2009), but also the avoidance response of the two tested soil-dwelling species (Natal-daLuz et al 2008). The heterogeneity of the soil inside the smelter area can be related to the failed attempt to encapsulate the tailings by depositing thousands of cubic meters of soil from regions around (Anjos 2003).…”
Section: Soil Properties and Selection Of Reference Soilsmentioning
confidence: 99%
“…However, for practical reasons both species are still widely used for these purposes due to their short reproduction time, easy handling in laboratory and the wealth of information on their sensitivity to various types of pollutants (Udovic and Lestan, 2010;Gomez-Eyles et al, 2011;Kinney et al, 2012;Wang et al, 2012). Nevertheless, the testing of natural soil or tropical artificial soil (TAS; Garcia et al, 2004) and earthworm species found in tropical areas (particularly geophagous endogeics that are dominant in tropical soils; Lavelle, 1983) in toxicity tests could contribute to a more relevant and reliable risk assessment of chemicals in the tropics (Kuperman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…O substrato utilizado para validar os testes foi um solo artificial, em que a formulação original foi modificada, com utilização da fibra de coco no lugar da turfa, diminuindo seu conteúdo para 5 %, denominado de solo artificial tropical (SAT) (Kuperman et al, 2009). A fibra de coco foi utilizada em virtude de ser um material barato, de fácil obtenção e maior disponibilidade.…”
Section: Parâmetros Gerais Dos Testesunclassified